2016
DOI: 10.1039/c6sc00432f
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and properties at a sub-nanometer scale

Abstract: Ultrathin materials at a sub-nanometer scale not only feature atomic scale size, but also possess unprecedented properties compared to conventional nanomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 94 publications
0
60
0
Order By: Relevance
“…The Fe 3 O 4 @snPt catalyst exhibited the excellent catalyst for this reaction, the catalytic activity decreased (entries 14-15) after four cycles. As we used other solvents for this catalytic system, such as EtOH, MeOH, and isopropanol, the catalytic activity was not satisfied (entries [16][17][18]. The hydrogen sources were also explored and the results showed that other reductants were not much suitable for this catalytic system (entries [19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Fe 3 O 4 @snPt catalyst exhibited the excellent catalyst for this reaction, the catalytic activity decreased (entries 14-15) after four cycles. As we used other solvents for this catalytic system, such as EtOH, MeOH, and isopropanol, the catalytic activity was not satisfied (entries [16][17][18]. The hydrogen sources were also explored and the results showed that other reductants were not much suitable for this catalytic system (entries [19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…All of the halo-nitroarenes were catalytic transfer hydrogenated to the corresponding anilines in a few minutes (entries 4-9). Then, this Fe 3 O 4 @snPt@PCN catalyst was also used to the catalytic transfer hydrogenation of nitroarenes with other functional groups, such as, hydroxyl, carboxyl, ester group, ether, amide, amino group, and olefin (entries [10][11][12][13][14][15][16][17][18][19][20]. The reaction results indicated that all the functional nitroarenes were successfully transformed to the corresponding anilines with high conversion and selectivity (>99%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the size of conventional nanomaterial is reduced to the level of molecule, the gap might be bridged. Thanks to the advances in synthesis, inorganic nanomaterials with size confined at the level of a single‐unit cell of crystals or molecular level have been prepared recently, and some unprecedented properties have been observed …”
Section: Introductionmentioning
confidence: 99%
“…Understanding the size‐dependent properties of nanomaterials is one of the essential targets in nanoscience. To specify the unique size‐dependent properties at the size gap between molecule and conventional nanomaterials, and the research interest in materials with size confined at the level of a single‐unit cell or molecular level, a pragmatic term “sub‐nanometric material (SNM)” is suggested . The novelty of SNM lies on both the observed interesting properties and the creative understanding of inorganic materials.…”
Section: Introductionmentioning
confidence: 99%